STUDI PERBANDINGAN TERHADAP HAK WARIS ANAK YANG LAHIR TANPA PERKAWINAN ORANG TUA MENURUT HUKUM PERDATA DAN HUKUM ISLAM - Sari, Alma Nofita; Septiandani, Dian; Astanti, Dhian Indah (Fakultas Hukum, Universitas Semarang, 2024)
Inheritance in Indonesia recognizes the existence of 2 (two) legal systems, namely according to the Civil Code and Islamic Law. The two legal systems have different perspectives, especially regarding the status of illegitimate children. The Constitutional Court's decision adds complexity by recognizing the civil relationship of an illegitimate child with the biological father through scientific and technological evidence. This research aims to determine the inheritance rights of children without married parents according to the Civil Code and Islamic Law and to determine the recognition of children without married parents according to the Civil Code and Islamic Law. This research uses a type of normative research with analytical descriptive specifications with library study data collection focusing on secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Based on the research results, it was concluded that the recognition of children without married parents according to the Civil Code and Islamic Law has differences in approach. The Civil Law, through articles 272 and 280, regulates the recognition of children without marriage under certain conditions. This involves marriage licenses, mutual obligations, guardianship, and inheritance rights. Meanwhile, Islamic law states that children of adultery are illegitimate and cannot be assigned to their father. Civil Law focuses more on civil status and rights, while Islamic Law emphasizes the validity of marriage and family honor in a religious context. Then the Inheritance Rights for Children without Their Parents' Marriage According to the Civil Code and Islamic Law have differences in that the Civil Code regulates children's inheritance rights in the context of kinship, with divisions based on kinship relations, bilateral principles and degrees. In contrast, Islamic law emphasizes the conditions for the validity of marriage as the basis for inheritance rights, following principles such as individual, bilateral and justice principles. AbstrakPewarisan di Indonesia mengenal adanya 2 (dua) sistem hukum yaitu menurut KUHPerdata dan Hukum Islam. Kedua sistem hukum memiliki perspektif yang berbeda terutama terhadap status anak diluar kawin. Keputusan Mahkamah Konstitusi menambah kompleksitas dengan mengakui hubungan perdata anak luar perkawinan dengan ayah biologis melalui bukti ilmu pengetahuan dan teknologi. Penelitian ini bertujuan untuk mengetahui hak waris bagi anak tanpa perkawinan orang tua menurut KUH Perdata dan Hukum Islam dan Untuk mengetahui pengakuan anak tanpa perkawinan orang tua menurut KUH Perdata dan Hukum Islam. Penelitian ini menggunakan jenis penelitian normatif dengan spesifikasi deskriptif analitis dengan pengumpulan data studi kepustakaan berfokus pada data sekunder terdiri atas bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier. Berdasarkan hasil penelitian disimpulkan Pengakuan anak tanpa perkawinan orang tua menurut KUH Perdata dan Hukum Islam memiliki perbedaan dalam pendekatan. Hukum Perdata, melalui pasal 272 dan 280, mengatur pengakuan anak tanpa perkawinan dengan syarat tertentu. Ini melibatkan izin kawin, kewajiban timbal balik, perwalian, dan hak waris. Sementara itu, Hukum Islam menyatakan anak zina tidak sah, tidak dapat dinasabkan kepada ayahnya. Hukum Perdata lebih fokus pada status keperdataan dan hak-hak, sedangkan Hukum Islam menekankan keabsahan pernikahan dan kehormatan keluarga dalam konteks agama. Kemudian Hak Waris Bagi Anak tanpa Perkawinan Orang tua Menurut KUHPerdata dan Hukum Islam memiliki perbedaan dimana KUH Perdata mengatur hak waris anak dalam konteks kekerabatan, dengan pembagian berdasarkan hubungan kekerabatan, asas bilateral, dan perderajatan. Sebaliknya, Hukum Islam menegaskan syarat sahnya perkawinan sebagai dasar hak waris, mengikuti prinsip-prinsip seperti asas individual, bilateral, dan keadilan.